Evaluation of four chemotherapy regimens for treatment of advanced AIDS-associated Kaposi sarcoma in Kenya: a cost-effectiveness analysis. Issue 8 (August 2022) - Freeman, Esther E; McCann, Nicole C; Semeere, Aggrey; Reddy, Krishna P; Laker-Oketta, Miriam; Byakwaga, Helen; Pei, Pamela P; Hajny Fernandez, Maya E; Kiprono, Samson; Busakhala, Naftali; Martin, Jeffery N; Maurer, Toby; et al.
Summary: Background: The most effective treatment for advanced AIDS-associated Kaposi sarcoma is paclitaxel or pegylated liposomal doxorubicin (PLD); neither is routinely used in sub-Saharan Africa due to limited availability and high cost. We examined the clinical impact, costs, and cost-effectiveness of paclitaxel or PLD in Kenya, compared with etoposide or bleomycin–vincristine. Methods: In this study, we use the Cost-Effectiveness of Preventing AIDS Complications (CEPAC)—International Model to project clinical outcomes and costs among people living with HIV and advanced Kaposi sarcoma on antiretroviral therapy. We compared four different treatment strategies: etoposide, bleomycin–vincristine, paclitaxel, or PLD. We derived cohort characteristics and costs from the Kenyan Academic Model for Providing Access to Healthcare network, and adverse events, efficacy, and mortality from clinical trials. We projected model outcomes over a lifetime and included life expectancy, per-person lifetime costs, and incremental cost-effectiveness ratios (ICERs). We conducted budget impact analysis for 5-year total costs and did deterministic and probabilistic sensitivity analyses to evaluate the effect of uncertainty in input parameters. Findings: We found that paclitaxel would be more effective than bleomycin–vincristine and would increase life expectancy by 4·2 years per person. PLD would further increase life expectancy by 0·6 years per person. Paclitaxel would be the most cost-effective strategy (ICER US$380 per year-of-life-saved compared with bleomycin–vincristine) and would remain cost-effective across a range of scenarios. PLD would be cost-effective compared with paclitaxel if its price were reduced to $100 per cycle (base case $180 per cycle). Implementing paclitaxel instead of bleomycin–vincristine would save approximately 6400 life-years and would increase the overall 5-year Kenyan health-care costs by $3·7 million; increased costs would be primarily related to ongoing HIV care given improved survival. Interpretation: Paclitaxel would substantially increase life expectancy and be cost-effective compared with bleomycin–vincristine for advanced AIDS-associated Kaposi sarcoma in Kenya and should be the standard of care. PLD would further improve survival and be cost-effective with a 44% price reduction. Funding: US National Institutes of Health and Massachusetts General Hospital. Translation: For the Swahili translation of the abstract see Supplementary Materials section.